Investigating primate densities and human-primate conflict in Tembaro Community Conserved Forest, Omo River Basin, Ethiopia - Meselech Anshebo; Aberham Megaze; Taye Dobamo (BMC Zoology)
Abstract Background Human-primate conflict is a global conservation challenge, particularly in densely populated, low-income countries like Ethiopia. The Omo River Valley forest belt, spanning across the Omo River in Ethiopia to Lake Turkana in Kenya, harbors a diverse array of African primate species. An investigation on non-human primate population density and human primate conflict was carried out from January 2022 to December 2023 in the Tembaro Community Conserved Forest, Omo River basin, South Central Ethiopia. The population density of non-human primates was estimated using distance sampling method, and the intensity of conflict among human-primate was quantified by a questionnaire survey and focus group discussions. Results The study revealed some interesting results which include the presence of black colobus monkeys (Colobus satanas) in Ethiopia. The mean density of Anubis baboons (Papio anubis) was 10.06 ± 2.93, grivet monkeys (Chlorocebus aethiops) 17.09 ± 4.53, black colobus monkeys (Colobus satanas) (vulnerable primate species in Africa) was 8.3 ± 1.20, and mantled guerezas (Colobus guereza) was 14.76 ± 3.57 individuals/km2. Crop damage and livestock predation were prevalent issues in the present study area. Majority of the local village respondents (51.96%, n = 146) reported that crop damage was the common cause of human-primate conflict, followed by livestock predation and crop damage (33.5%, n = 94). Majority of the conflict was caused by Anubis baboon (Papio anubis) (41%, n = 115), followed by grivet monkeys (Chlorocebus aethiops) (33.1%). The most common cultivated crop by farmers in the study area and the most damaged by the non-human primates was maize (Zea mays) (33.5%, n = 94). The average estimated loss of crops was US$ 6544.50 per year. The average annual loss incurred by each household due to primates predation on their small animals was 94.19 US$. Physical guarding (33%, n = 93) was chosen as the most effective strategy to prevent crop damage and livestock predation. Conclusion This study provides valuable insights into primate ecology and the challenges they pose to local communities. The findings reveal varying primate population densities, with Grivet monkeys exhibiting the highest densities. These primate densities contribute significantly to human-wildlife conflict, primarily through crop foraging and livestock predation. While traditional mitigation methods are currently in place, a more sustainable and integrated approach is urgently needed to ensure the harmonious coexistence of primates and local communities. The findings of this study are crucial for developing effective conservation and conflict mitigation strategies that will safeguard the long-term survival of both primates and the livelihoods of local people. Clinical trial number Not applicable.